Functional similarities between the protein O-Mannosyltransferases Pmt4 from Bakers' Yeast and human POMT1 - Bausewein, Daniela; Strahl, Sabine (The journal of biological chemistry, 2016)
Protein O-mannosylation is an essential post-translational modification. It is initiated in the endoplasmic reticulum by a family of protein O-mannosyltransferases that are conserved from yeast (PMTs) to human (POMTs). The degree of functional conservation between yeast and human protein O-mannosyltransferases is uncharacterized. In bakers' yeast, the main in vivo activities are due to heteromeric Pmt1-Pmt2 and homomeric Pmt4 complexes. Here we describe an enzymatic assay that allowed us to monitor Pmt4 activity in vitro. We demonstrate that detergent requirements and acceptor substrates of yeast Pmt4 are different from Pmt1-Pmt2, but resemble that of human POMTs. Furthermore, we mimicked two POMT1 amino acid exchanges (G76R and V428D) that result in severe congenital muscular dystrophies in humans, in yeast Pmt4 (I112R and I435D). In vivo and in vitro analyses showed that general features such as protein stability of the Pmt4 variants were not significantly affected, however, the mutants proved largely enzymatically inactive. Our results demonstrate functional and biochemical similarities between POMT1 and its orthologue from bakers' yeast Pmt4.